Greenie Kitchy Enterprise / Nurul Izzah Nor Hisham - Nor Hisham, Nurul Izzah (2020)
Greenie Kitchy Enterprise offers bakery product which is brownies and providing variety types of brownies that gives the high satisfaction of customers. Our clients is customers identifying as middle as middle and low class who want consume product with affordable price. Greenie Kitchy offers a variety of brownies that give nutrition of health, low sugar, low calories and receive halal certificates. In Bandar Baru Bangi, Greenie Kitchy Enterprise business has seen an explosion of growth over the year. Bangi is an area that many people live and it cause demand of brownies is rise over the year. Greenie Kitchy Enterprise marketing strategy is to emphasize the quality and price of our products. We offer the affordable price because many people can easily to buy it such as child, teenagers, adult people and more. Thus, we develop marketing strategy that gives attraction to people to come to our shop.